Application of response surface methodology (RSM) in analyzing the hydrolytic degradation of plasticized MWCNTs nanocomposites - H., Norazlina; A., Suhaila; M., Rabiatul Manisah; A., Nabihah; H., Lili Shakirah; M. S., Nurul Aniyyah; Y., Kamal (Institute of Physics, 2022)
The present research goals are to investigate how several parameters became the factor to maximize the degradation ability of biopolymer. Multi-walled carbon nanotubes (MWCNTs) was blended in poly(lactic acid (PLA) assisted by poly(ethylene glycol) (PEG) as a plasticizer. PLA/PEG/mCNTs from the melt blending technique was used for analysis in hydrolysis degradation purposely to discover how the time, temperature and pH of media solution could affect the weight loss and validate by Response Surface Methodology (RSM). The hydrolysis study was examined at three parameters of immersion; time from 7 to 28 days; the temperature at 25 °C, 45 °C and 65 °C; and pH of the solution at pH 3 (HCl), pH 6.5 (deionized water) and pH 10 (NaOH). The maximum weight loss, 22.53 % was observed after 28 days of immersion at 65 °C of immersion temperature and pH 3 of solution. The quadratic model developed was reasonably accurate based on the R2 value of 0.966, insignificant lack of fit, and low percentage error during validation experiment from the predicted values (< 5 %).